The Design of an Interprofessional Health Record Form for Diabetes Mellitus Care at Primary Health Care Facility: A Recommendation - Fitarina, Fitarina; Krismaningrum, Hasti Primadilla (Poltekkes Kemenkes Tanjung Karang, 2024)
This research focuses on the pillars of primary care transformation by increasing primary services' capacity and capability, especially Diabetes Mellitus (DM) care. The study aims to produce a recording form containing simple, interprofessional records of DM patient care that can be used by various professions and can be applied in multiple primary health facilities. The design was developed through a development research approach with stages of form modification, expert and practitioner review, revision, trial, focus group discussion, and final revision. The trial was carried out by Community Health Center (Puskesmas) nurses in services at the Puskesmas through home visits for DM patients, Posbindu services, and outpatient care. Data from expert opinions, user opinions, and observations of the forms tested were analyzed qualitatively using the Technology Acceptance Model concept approach. The resulting form consists of two pages containing primary patient data and daily progress notes in tabular form. Research participants showed positive beliefs, attitudes, and behavior toward the forms being tested—the actual use of the form on an average of 3 patients per participant. The completeness was 90 percent filled. They expressed their intention to use the form further and recommended widespread dissemination to implement it in practice. The form is acceptable and ready to be applied for outpatient care, health monitoring, and home care for DM cases. Recommendations can be given to policymakers and health service providers to implement in services. Apart from that, the form can be further developed in electronic form by information technology developers.